A Forward Current-Voltage-Temperature Method for Extraction of Intrinsic Schottky Barrier Height. (21st July 2020) - Changshi, Liu
Abstract : Schottky Barrier Height, SBH, controls the current flow into electronic and photoelectronic devices based on hetero-junctions. The SBH predicted via the conventional method is sensitive to temperature by forward current-voltage-temperature, I-V-T. This poses some problems in applications of a hetero-junction device. Therefore, one looks for a technique to extract intrinsic SBH of each new hetero-junction. This paper established a simple model for determination of the forward I-V-T characteristics, a real thermionic current, Itc, and SBH. This model was introduced by considering quantum statistics and phenomenological. The proposed methodology can couple two independent plots of each hetero-junction current and helps predict the value of current at any measurement condition. The proposed model was successfully validated via over twenty experimental I–V curves. Therefore, applying the least-squares nonlinear fitting to extract the parameters of the proposed model on Itc -T yields the values of the intrinsic SBH. The results of applications on four hetero-junctions prove that the proposed method is credible in this paper.